2016
DOI: 10.1016/j.atmosenv.2015.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in the atmosphere and in rainwater at Cape Point, South Africa

Abstract: Mercury measurements were concurrently made in air (Gaseous Elemental Mercury, i.e. GEM) as well as in precipitation samples (Total mercury, i.e. TotHg) over a seven year period (2007-2013) at Cape Point, South Africa, during the rainy seasons (May-October). Eighty-five rain events, almost exclusively associated with cold fronts, have been identified of which 75% reached the Cape Point observatory directly across the Atlantic Ocean from the south, while 19% moved in to the measuring site via the Cape Town metr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Within tropical regions, wet deposition has been shown to be a significant pathway for mercury from the atmosphere to both oceanic and terrestrial ecosystems, even in relatively low-mercury air and despite the low solubility of mercury in its elemental form (Fostier et al, 2000;Costa et al, 2012;Hansen and Gay, 2013;Soerensen et al, 2014;Shanley et al, 2015). Mercury "rainout" -or the tendency for mercury rainwater loading to decrease with increasing precipitation -has also been demonstrated in Mercury Deposition Network (MDN) data in North America (Glass and Sorensen, 1999;Prestbo and Gay, 2009) and positive correlations between GEM (TGM) and rainwater mercury have been reported in MDN data (GEM; Cole et al, 2014) and at Cape Point, South Africa (TGM; Brunke et al, 2016). Re-emission of any deposited mercury is likely to be inhibited throughout the wet season, as it has been shown that GEM emission from background mercury soils is suppressed when the soils are saturated (Briggs and Gustin, 2013).…”
Section: Overall Means and Seasonal Trendsmentioning
confidence: 95%
“…Within tropical regions, wet deposition has been shown to be a significant pathway for mercury from the atmosphere to both oceanic and terrestrial ecosystems, even in relatively low-mercury air and despite the low solubility of mercury in its elemental form (Fostier et al, 2000;Costa et al, 2012;Hansen and Gay, 2013;Soerensen et al, 2014;Shanley et al, 2015). Mercury "rainout" -or the tendency for mercury rainwater loading to decrease with increasing precipitation -has also been demonstrated in Mercury Deposition Network (MDN) data in North America (Glass and Sorensen, 1999;Prestbo and Gay, 2009) and positive correlations between GEM (TGM) and rainwater mercury have been reported in MDN data (GEM; Cole et al, 2014) and at Cape Point, South Africa (TGM; Brunke et al, 2016). Re-emission of any deposited mercury is likely to be inhibited throughout the wet season, as it has been shown that GEM emission from background mercury soils is suppressed when the soils are saturated (Briggs and Gustin, 2013).…”
Section: Overall Means and Seasonal Trendsmentioning
confidence: 95%
“…Therefore, here we only briefly introduce the spatial distribution of forest Hg deposition. South America was estimated to bear the highest litterfall Hg deposition (65.8 ± 57.5 µg m −2 yr −1 ) around the world (Teixeira et al, 2012(Teixeira et al, , 2017Buch et al, 2015;Fostier et al, 2015;Fragoso et al, 2018;Shen et al, 2019). There have been numerous forest Hg deposition studies in the recent decade in East Asia with the second highest average litterfall Hg deposition flux (35.5 ± 27.7 µg m −2 yr −1 ) (Wan et al, 2009;Wang et al, 2009;Fu et al, 2010aFu et al, , b, 2016aGong et al, 2014;Luo et al, 2016;Ma et al, 2015Ma et al, , 2016Han et al, 2016;Wang et al, 2016b;Zhou et al, 2016Zhou et al, , 2017.…”
Section: Forest Depositionmentioning
confidence: 99%
“…Brunke et al [] noticed that the annual average mercury concentrations in the atmosphere and in rainwater at Cape Point, South Africa, correlate with annual precipitation depth which in turn is also influenced by ENSO in southern Africa. This finding prompted us to analyze several atmospheric mercury data sets in detail, each of which encompasses more than 8 years of measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Because biomass burning is one of the major sources of atmospheric CO, CH 4 , CH 3 Cl, and many other trace gases and aerosols [Andreae and Merlet, 2001], the observed interannual variations of many of these gases could be shown to be driven by ENSO [e.g., Wang et al, 2004;Simmonds et al, 2005;Logan et al, 2008;Chandra et al, 2009;Voulgarakis et al, 2010;Inness et al, 2015]. Brunke et al [2016] noticed that the annual average mercury concentrations in the atmosphere and in rainwater at Cape Point, South Africa, correlate with annual precipitation depth which in turn is also influenced by ENSO in southern Africa. This finding prompted us to analyze several atmospheric mercury data sets in detail, each of which encompasses more than 8 years of measurements.…”
Section: Introductionmentioning
confidence: 99%